GAMBARAN PERILAKU MALADAPTIF ANAK PRASEKOLAH KB-TK ‘AISYIYAH DI SIDOARJO PASCA COVID-19: MENGGUNAKAN METODE ANALISIS RASH - Ainiyah, Siti Umrotul; Widyastuti, Widyastuti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
The maladaptive behavior of preschoolers has been in the spotlight during the Covid-19 pandemic. Behavior that shows the child is unable to adapt according to the stages of development of his age. The problems that arise can hinder the achievement of optimal child development. The purpose of this study was to describe the maladaptive behavior of 'Aisyiyah KB-TK preschool children in Sidoarjo post-covid-19. This study uses a non-experimental quantitative method. The population in this study were mothers of preschool children (age 3-6 years) with a total of 205. The total sample was 205 using a convenience sampling technique. The data measurement tool uses the adaptation instrument from the Strength and Difficulties Questionnaire (SDQ) to see maladaptive behavior of preschoolers. The data analysis used in this study was the RASH model to see a picture of maladaptive behavior of preschoolers with the help of WINSTEPS version 3.37 to determine the reliability and validity of the research instrument. The results of the analysis show that the average measurement value (in logit) for a person is -1.54 logit. The average value lower than logit 0.006 indicates that most of the 'Aisyiysh KB-TK preschool children in Sidoarjo do not show maladaptive behavior.